Computational analyses of passive wet gas separation in branched piping - Pao, W. (EDP Sciences, 2014)
Understanding the behavior of two-phase flow through a T-junction is very important as it could potential contribute to massive cost saving in partial phase separation. The objectives of this paper focuses on the effect the inlet flow conditions on two-phase split efficiency under constant pressure gradient, and the effect of averaged bubble diameter on the mass flow split at the side arm outlet Via computational fluid dynamics tool, preliminary investigation found that beyond side to main arm diameter ratio of 0.75, there is a drop of separation efficiency. The change of fraction of gas taken off is almost linearly and negatively proportional to the unit increment of initial gas saturation. When the side to main arm diameter ratios equal to 0.5 and 0.75, the fraction of gas taken off is almost similar as far as the initial gas saturation is concerned. Â© 2014 Owned by the authors, published by EDP Sciences.